KEFIR OF KEJI BELING TEA (Strobilanthes crispus) AS FUNCTIONAL BEVERAGE FOR GLUCOSE INTOLERANCE - Pramita Laksitarahmi Isrianto (International Journal of Applied Biology, 2020)
Kefir is beverage fermented product, it is usually made from milk. However, there is an arising concern about lactose intolerant. Therefore, taking benefit of herbal tea solution as raw material of kefir will give multiple benefits. The used tea solution was made from keji beling leaves (Strobilanthes crispus L.) which has many benefits. Kefir beverage is probiotic beverage which is beneficial for digestion health and can keep immune system, as well as keji beling tea which is rich in antioxidants. The used design in this research was Complete Randomized Design (Rancangan Acak Lengkap) with 4 levels of treatment namely: concentration of keji beling 0%, 10% and 15% with fermentation duration of 12 hours and 24 hours. Based on the research result pointed out the obvious effect between treatment toward pH, total polyphenols, total acetic acid, and total glucose with p score = 0,00. The result of lactic acid bacteria (BAL) total is 1,914 x107 CFU/mL and yeast total is 1,532 x 107 CFU/mL on concentration of 15% kefir of keji beling tea with fermentation duration of 24 hours. Result for organoleptic test shows the obvious effect (p=0,00) between the treatment toward parameters of taste, aroma, color and power. Panelist takes pleasure on the treatment P1 with concentration of horsewhip tea 150% in fermentation duration of 24 hours. Key words : Kefir, Keji beling tea (Strobilanthes crispus L), Fermented Beverage.